Free-Breathing Dynamic Contrast-Enhanced Imaging of the Upper Abdomen Using a Cartesian Compressed-Sensing Sequence With Hard-Gated and Motion-State-Resolved Reconstruction. Issue 11 (November 2019) - Hausmann, Daniel; Niemann, Tilo; Kreul, Diana; Nocito, Antonio; Klarhöfer, Markus; Nickel, Dominik M.; Kiefer, Berthold; Attenberger, Ulrike I.; Zöllner, Frank G.; Kubik-Huch, Rahel A.
Abstract : Objectives: The aim of this study was to compare a compressed-sensing free-breathing VIBE (fbVIBE) with a conventional breath-hold VIBE (bhVIBE) for dynamic contrast-enhanced imaging of the upper abdomen. Materials and Methods: In total, 70 datasets (bhVIBE, n = 30; fbVIBE n = 40; hard-gated [hg] reconstruction, n = 30; motion-state-resolved [mr] reconstruction, n = 10) were assessed by 2 experienced readers. Both sequences were performed on 1.5-T magnetic resonance imaging scanners. The prototypical fbVIBE sequence acquired a navigation signal along with the imaging data and supported 2 different reconstructions: an hg reconstruction that either accepted or rejected an echo train based on the navigation signal and an mr reconstruction that assigned echo trains to their determined motion states. The hg reconstruction to reduce respiratory motion artifacts was carried out inline on the scanner (duration: approximately 8 minutes on the scanner-integrated CPU). The mr reconstruction delivered better results, but the reconstruction time is multiplied by the number of selected motion states (6 in the current study). Comparable reconstruction times to hg reconstruction can only be achieved on GPU-supported scanners. Therefore, the acquired raw data were selectively reconstructed at a later timepoint (duration: approximately 45 minutes). Welch analysis of variance tests were applied to compare image quality (IQ), delineation of structures, artifacts, and diagnostic confidence, which were rated on Likert-type scales (IQ/delineation of structures/diagnostic confidence: 1 [nondiagnostic] to 5 [perfect]; artifacts: 1 [no artifacts] to 5 [severe artifacts]). Mann-Whitney U tests and Kruskal-Wallis H tests were used to compare the extent of artifacts in older (aged ≥70 years) and younger (aged <70 years) patients. Interobserver agreement was assessed using Cohen κ. Results: Mean ratings for IQ/delineation of structures/diagnostic confidence of fb(hg)VIBE (4.2 ± 0.7/4.3 ± 0.8/4.3 ± 0.7; κ = 0.8/0.7/0.6) and fb(mr)VIBE (4.9 ± 0.3/4.9 ± 0.3/4.9 ± 0.3; κ = 0.3/1/0.9) were higher compared with those of bhVIBE (3.7 ± 0.8/3.8 ± 0.8/3.9 ± 0.9; κ = 0.9/0.9/0.9), whereas artifacts of fb(hg)VIBE/fb(mr)VIBE were rated lower (fb[hg]VIBE/fb[mr]VIBE/bhVIBE = 2.2 ± 0.9/1.3 ± 0.5/2.4 ± 0.9; κ = 0.6/0.6/0.9). The IQ of fb(hg)VIBE was rated significantly higher compared with that of bhVIBE ( P = 0.03). All parameters were significantly improved by mr reconstruction compared with fb(hg)VIBE and bhVIBE ( P < 0.001). In the fb(hg)VIBE cohort, an insignificant trend toward lower artifacts in the younger age group (≥70 years: 2.5 ± 0.9 vs <70 years: 1.9 ± 0.8) was found, whereas significant differences emerged in the bhVIBE cohort (≥70 years: 3 ± 0.9 vs <70 years: 2.1 ± 0.9; P = 0.02). Conclusions: Fast fbVIBE using hg and mr reconstructions is technically feasible with improved IQ compared with that of bhVIBE. Free-breathing VIBE may be useful for dynamic contrast-enhanced of the upper abdomen, particularly in older and/or severely ill patients with impaired breath-hold capabilities.